(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the meaning of the translation of the work “Tarikh-i-Rashidi”. It will be discussed a version about the rich history, literary and cultural significance of our former classical literature, translated into a modern literary language for the Uzbek reader. It will be shown how some important information in the work is translated into English and Russian. The meaning of phraseological units in the work in these four variants is analysed.